Risk Communication Strategies Used During the Rising Water Levels Around Kenya’s Lake Naivasha - Iminza Turere; Robert Nyaga (Communicare)
Risk communication is critical to providing a scientific understanding of perceptions and responses to climate change threats. Using seven focus discussion groups comprising 75 participants, this study examined the role of risk communication in effective implementation of climate change adaptation during floods experienced around Lake Naivasha basin in Kenya in 2018. Specifically, within the contexts of Protective Action Decision Model and risk communication in relation to flood occurrences, the study investigated the following: knowledge and awareness of climate change, risk communication systems put in place to enhance adaptive behaviour and whether the risk communication systems in place were viewed as effective. Findings revealed that the participants understood what climate change is, and related it to their own experiences. In addition, as there was no clear communication before the floods occurred, the risk communication systems were seen as not effective enough, even though the participants received warnings about the imminent rise of water levels in the freshwater lake.